(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article states that teaching the Russian language and literature in a modern pandemic in a new way, without abandoning the traditional process with the help of modern technologies. In addition, methods of teaching the Russian language and literature based on pedagogical technologies in the process of distance learning were identified.